Black Patients Experience Highest Rates of Cancer-associated Venous Thromboembolism. (February 2020) - Addo-Tabiri, Nana Oduraa; Chudasama, Rani; Vasudeva, Rhythm; Leiva, Orly; Garcia, Brenda; Ravid, Jonathan D.; Bunze, Tamala; Rosen, Linda; Belghasem, Mostafa; Francis, Jean; Brophy, Mary; Johnson, Brett; et al.
Abstract : Purpose: Cancer patients are at a higher risk of venous thromboembolism (VTE) than the general population. In the general population, blacks are at a higher risk of VTE compared with whites. The influence of race on cancer-associated VTE remains unexplored. We examined whether black cancer patients are at a higher risk of VTE and whether these differences are present in specific cancer types. Design: A retrospective study was performed in the largest safety net hospital of New England using a cohort of cancer patients characterized by a substantial number of nonwhites. Results: We identified 16, 498 subjects with solid organ and hematologic malignancies from 2004 to 2018. Among them, we found 186 unique incident VTE events, of which the majority of the events accrued within the first 2 years of cancer diagnosis. Overall, blacks showed a 3-fold higher incidence of VTE (1.8%) compared with whites (0.6%; P <0.001). This difference was observed in certain cancer types such as lung, gastric and colorectal. In lung cancer, the odds of developing VTE in blacks was 2.77-times greater than those in white patients (confidence interval, 1.33-5.91; P =0.007). Despite the greater incidence of cancer-associated VTE in blacks, their Khorana risk score of VTE was not higher. Conclusions: In a diverse cancer cohort, we observed a higher incidence of cancer-associated VTE in blacks compared with patients from other races. This study indicates the consideration of race in the risk assessment of cancer-associated VTE. It could also lead to future mechanistic studies aiming at identifying reasons for differential VTE risk depending on cancer type. Abstract : Supplemental Digital Content is available in the text.